TRANSLATORS AND INTERCULTURAL COMMUNICATION (REVISTA DE HUMANIDADES Y CIENCIAS SOCIALES Y MULTIDISCIPLINARIA, 2021)
The translator plays a very important role within a global society. He/she enables the establishmentof relations among people with different backgrounds and languages. When doing so, he/she is takingpart in the cycle of communication, where the characters of author, translator and reader areinterchangeable. The aim of this article is to discuss the role of the translator in the society as well asto describe and analyse the expert knowledge he has to acquire in order to perform a good job.